REPRODUCTIVE RECORD OF CHARADRIUS VOCIFERUS (LINNAEUS 1758, KILLDEER) IN PARAISO WETLAND, HUACHO (LIMA – PERU) - Chávez-Villavicencio, César (2015)
We report the record of a Charadrius vociferus (Charadriiformes: Charadriidae; killdeer) nest in Paraíso wetland located in Huacho (Lima – Peru) (11°12'54"S, 77°35'16"W), containing four eggs, one of which was in the process of hatching.